Why teaching innovation matters: Evidence from a pre- versus peri-COVID-19 pandemic comparison of student evaluation data - Lin, Pei-Hsin; Huang, Lee-Rong; Lin, Sheng-Hsiang (Frontiers in Psychology, 2022)
The Covid-19 pandemic has robustly affected global education environments, so higher education institutions need to emphasize innovation and creativity in educational methods for teachers to improve their teaching performance as well as enhance engagement and motivation of student in this changing environment. Accordingly, it is essential to discuss the role of teaching innovation in the setting of the Covid-19 pandemic compared to the pre-Covid-19 period. The aim of this study is to empirically validate the importance of teaching innovation on student evaluation of teaching before and during the Covid-19 pandemic. Data were collected from the medical college of a comprehensive university in Taiwan and subjected to t-tests and multiple linear regression analysis. Findings from a quantitative research with 44 teachers reveal that teaching innovation was positively correlated to student evaluation of teaching. We also found that teachers who implement teaching innovation strategies were performed better than those teachers who use conventional teaching strategies on student evaluation of teaching. In particular, teaching innovative teachers had improvement in student evaluation of teaching during the time of Covid-19 pandemic, but not to non-teaching innovative teachers. The evidence from this study suggests that teaching innovation not only can enhance teachers’ teaching development and performance but also boost students' motivation for learning, especially in the time of Covid-19 pandemic. Our findings have important implications for future research on teaching innovation and for higher education institutions and faculty wishing to provide high-quality learning environments to their students.